Plication without degloving – Safe and effective approach for correcting lateral and dorsal penile curvature: Case series - Hüseyin Cihan Demirel; Cumhur Yeşildal; Musab Ilgi; Ahmet Tevfik Albayrak; Emre Aykanlı; Sinan Levent Kireççi (Urology Annals, 2019)
Penile curvature deformities are often manageable with surgical reconstruction methods. We aimed to show the safety and efficacy of ventral and dorsal plication techniques without degloving in our two patients who have penile curvature. Two young adults, aged 20 and 23 years, presented to our clinic with lateral and dorsal penile curvatures. This problem has been sustaining since their teenage. Following the required preparations, two surgical techniques were used, namely Nesbit and Lue's “16-dot” technique. Patients completed a satisfaction survey at a mean of 6 months later the surgery. Although both patients reported a subjective decrease in penile length, their satisfaction rate was high. Penile plication without degloving is a safe and effective technique for correcting dorsal and lateral penile curvatures.